How Many Robocalls are too Many? Results from a Large-Scale Field Experiment. Issue 4 (1st October 2020) - Zelizer, Adam
Abstract : This study evaluates the turnout effects of automated telephone calls placed to voters in advance of the 2016 Texas primary election. Voters in 23 state legislative districts were assigned to receive between zero and seven calls from an interest group encouraging them to vote in the election. Automated calls raise turnout, with turnout appearing to increase in the number of assigned calls. Results mirror those in previous studies that send increasing amounts of get-out-the-vote mail and find that turnout effects decline after five to six "touches" from a campaign.